Yulangsan polysaccharide improves redox homeostasis and immune impairment in d-galactose-induced mimetic aging. Issue 5 (13th May 2015) - Doan, Van Minh; Chen, Chunxia; Lin, Xing; Nguyen, Van Phuc; Nong, Zhihuan; Li, Weisi; Chen, Qingquan; Ming, Jianjun; Xie, Qiuqiao; Huang, Renbin
<x xml:space="preserve">Abstract</x> Yulangsan polysaccharide (YLSP) is a traditional Chinese medicine used in long-term treatment as a modulator of brain dysfunction and immunity.